2003
DOI: 10.1592/phco.23.2.222.32092
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Herbal Use in Children with Attention‐Deficit—Hyperactivity Disorder or Depression

Abstract: Most caregivers supervised herbal therapy in their children, without communication with a health professional. A need exists for better communication between health professionals and caregivers regarding the use of herbal therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 28 publications
3
18
1
Order By: Relevance
“…More than 46% of the children from the urban and industrialised area of greater Milan making up our study population received CAM, a percentage that is similar to that found by other authors in children with chronic or recurrent diseases, and higher than that usually observed in the general paediatric population (1)(2)(3)(4)(5)(6)(7)(8)(9). Although CAM use can significantly vary from country to country so that the data derived from this study cannot be generalized, they seem to confirm the view that parents se1f-prescribe or agree with a paediatrician's prescription of CAM mainly when they have to face well-known clinical situations for which conventional medicine does not offer any definite solutions.…”
Section: Discussionsupporting
confidence: 89%
“…More than 46% of the children from the urban and industrialised area of greater Milan making up our study population received CAM, a percentage that is similar to that found by other authors in children with chronic or recurrent diseases, and higher than that usually observed in the general paediatric population (1)(2)(3)(4)(5)(6)(7)(8)(9). Although CAM use can significantly vary from country to country so that the data derived from this study cannot be generalized, they seem to confirm the view that parents se1f-prescribe or agree with a paediatrician's prescription of CAM mainly when they have to face well-known clinical situations for which conventional medicine does not offer any definite solutions.…”
Section: Discussionsupporting
confidence: 89%
“…The drug is labeled in Germany for the treatment of children 12 years and above and is often indicated for depression and related disorders, including anxiety and irritability. Hypericum is available in both prescription and over-the-counter products, and most of it is used as self-medication (Beckmann et al 2000;Cala et al 2003).…”
Section: Introduction R Ecent Policy Developments By the Europeanmentioning
confidence: 99%
“…In the general pediatric population, studies show that the majority of parents do not disclose CAM use to their child's HCP (Cala, Crismon, & Baumgartner, 2003;Crawford et al, 2006;Heuschkel et al, 2002;Lanski, Greenwald, Perkins, & Simon, 2003;Madsen et al, 2003;Ottolini et al, 2001;Pitetti, Singh, Hornyak, Garcia, & Herr, 2001;Sawni-Sikand, Schubiner, & Thomas, 2002;Spigelblatt & Laine-Ammara, 1994;Wilson & Klein, 2002). The most frequently reported barriers to CAM disclosure, among the general population as well as families with children, were a feeling that the HCP did not need to know about CAM use, fear of a negative response from the HCP, and the HCP did not ask (Prussing, Sobo, Walker, Dennis, & Kurtin, 2004;Robinson & McGrail, 2004;Shaw, Thompson, & Sharp, 2006).…”
mentioning
confidence: 99%